Determinação estatística do número de amostras simples de solo por área para avaliação de sua fertilidade - Barreto, Antônio Carlos; Ferreira de Novais , Roberto; Braga , José Mário (Revista Ceres, 2025)
This study reports the determination of the number of single samples used to constitute a compgsed sample/ha, through the statistical formula n = (t a .CV/f)2. The number of single samples was computed for several percentages of variation around the mean at t = 5%. The soil samples were collected form level ground, red yellow podzolic-latosol,located in Viçosa country, in the State of Minas Gerais. One hundred single samples were drawn from each area. The sampling sites were established by using the intersec- tions of a 10 x 10 meter coordinate system. Each sample was assayed for pH, P, Ca + Mg, Al and K.